2002
DOI: 10.1016/s0014-2999(02)01902-7
|View full text |Cite
|
Sign up to set email alerts
|

Fibrates suppress chenodeoxycholic acid-induced RANTES expression through inhibition of NF-κB activation

Abstract: Fibrates, hypolipidemic agents, are reported to be effective in treatment of primary biliary cirrhosis. However, the mechanism involved in therapeutic benefits of fibrates in primary biliary cirrhosis remains unknown. In contrast, hepatic regulated upon activation, normal T-cell expressed and secreted (RANTES) is increased in patients with primary biliary cirrhosis and bile acids up-regulate RANTES expression in hepatocytes. The role of fibrates in bile acid-induced RANTES expression was investigated in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…Blockade of CCR1 with the CCR1-specific antagonist BX471 substantially reduced interstitial leukocyte accumulation and fibrosis in mice with glomerulosclerosis and nephrotic syndrome (41). Our observations demonstrating that the use of a PPAR␣ ligand WY significantly inhibited cisplatin-induced upregulation of RANTES, and RANTES's recep- tors CCR1 and CCR5 are in agreement with those previous studies where fibrates were shown to repress TNF-␣ and bile acids induced RANTES expression in human hepatocytes through inhibition of both DNA binding activity and transcriptional activation of NF-B (22,24). Nevertheless, our studies cannot rule out the possibility that other inflammatory cells such as macrophages or T cells, in addition to neutrophils, participate in the inflammatory process associated with cisplatin nephrotoxicity.…”
Section: Role Of Inflammation In Cisplatin-induced Injurysupporting
confidence: 91%
“…Blockade of CCR1 with the CCR1-specific antagonist BX471 substantially reduced interstitial leukocyte accumulation and fibrosis in mice with glomerulosclerosis and nephrotic syndrome (41). Our observations demonstrating that the use of a PPAR␣ ligand WY significantly inhibited cisplatin-induced upregulation of RANTES, and RANTES's recep- tors CCR1 and CCR5 are in agreement with those previous studies where fibrates were shown to repress TNF-␣ and bile acids induced RANTES expression in human hepatocytes through inhibition of both DNA binding activity and transcriptional activation of NF-B (22,24). Nevertheless, our studies cannot rule out the possibility that other inflammatory cells such as macrophages or T cells, in addition to neutrophils, participate in the inflammatory process associated with cisplatin nephrotoxicity.…”
Section: Role Of Inflammation In Cisplatin-induced Injurysupporting
confidence: 91%
“…The maintenance of intestinal homeostasis is complex and involves interactions among the intestinal microflora, the epithelium and the host immune system. It has previously been shown that the leukotriene B 4 -PPARα pathway controls inflammation [7] and that PPARα ligands inhibit the migration of inflammatory cells [8]. In addition, we have reported that a PPARγ ligand inhibited the immunological functions of macrophages [9,10].…”
Section: Introductionmentioning
confidence: 75%
“…Bezafibrate and fenofibrate decrease the chenodeoxycholic acid- and tumor necrosis factor-α-induced mRNA expression and production of RANTES protein in human hepatoma cells [30, 31]. These findings indicate that fibrates may inhibit inflammatory cell migration by RANTES to the liver in patients with PBC.…”
Section: Discussionmentioning
confidence: 99%